The Unique Bipolar Clavicle Dislocation: A Novel Reconstruction Technique and Case Report. (11th August 2020) - Dev, Ameesh; Prabhakar, Gautham; Dutta, Anil; Dang, Khang
Abstract : A bipolar clavicle separation is defined as a simultaneous dislocation of the ipsilateral sternoclavicular joint (SCJ) and acromioclavicular joint (ACJ). This rare injury pattern is usually the result of a high-energy mechanism, such as a motor vehicle collision or fall from height. While there are several treatment options such as screw fixation, sutures, or plate fixations, there is no single standard approach for this infrequent injury. We describe a unique case of bipolar clavicle dislocation, specifically an anteriorly displaced SCJ and posteriorly displaced ACJ, treated with a novel surgical technique—a TightRope technique (Arthex®) and semitendinosus allograft.